Initiator-free crosslinking of oxetane functionalized low bandgap polymers: an approach towards stabilized bulk heterojunction solar cells. Issue 43 (25th October 2016) - Knauer, Philipp; Hahn, Tobias; Köhler, Anna; Strohriegl, Peter
Abstract : We report the synthesis of crosslinkable derivatives of the low bandgap polymer PFDTBT, poly(2, 7-(9, 9-dialkylfluorene)- alt -(5, 5-(4′, 7′-di-2-thienyl-2′, 1′, 3′-benzothiadiazole))), and the stabilization of BHJ solar cells by initiator-free crosslinking of oxetanes. Abstract : A critical issue of bulk heterojunction (BHJ) solar cells is the instability of the morphology of the polymer:fullerene blend over long operation times. We report the synthesis of crosslinkable derivatives of the low bandgap polymer PFDTBT, poly(2, 7-(9, 9-dialkylfluorene)- alt -(5, 5-(4′, 7′-di-2-thienyl-2′, 1′, 3′-benzothiadiazole))), and the stabilization of BHJ solar cells by crosslinking. Oxetane units are attached to the polymer side chains as crosslinkable functional groups. We study the crosslinking of the polymers via cationic ring opening polymerization of the oxetanes and show that our materials rapidly form insoluble networks. Our materials also crosslink in the presence of fullerenes. We report for the first time that crosslinking takes place upon prolonged heating to 100 °C without any added initiator. The best efficiency and thermal stability are found in thermally crosslinked BHJ solar cells. After 30 hours at 100 °C, 65% of the initial efficiency are retained and no further decay is observed up to 100 hours.